Mengimplementasikan Model Manajemen Terpadu untuk Pendidik dan Tenaga Kependidikan yang Berdaya Saing di SMP Negeri 28 Surabaya - Oktrian, Tiar Aisyana Silvy; Nurhalizah, Shinta; Windasari, Windasari (TSAQOFAH, 2024)
This research aims to explore the management of educators and educational staff at SMP NEGERI 28 Surabaya and to design an integrated management model that can enhance their competitiveness in the future. Qualitative research methods are employed, involving interviews and observations with school principals, teachers, and educational staff. Data analysis highlights key challenges, including adaptation to changes in educational policies and technological advancements. The research findings emphasize the importance of integrating various aspects of school management with current educational needs, as well as the role of educational information systems such as Dapodik in the integrated management model. In conclusion, the development of this model requires collaboration among stakeholders, effective communication, and competency enhancement to ensure successful implementation. It is hoped that this integrated management model can address the challenges faced by SMP NEGERI 28 Surabaya and enhance the overall quality of education.